Integral practice of the architects. The CUJAE experience - González Moreno, Maritza (Universidad de Cuenca, 2016)
The aim of this study is to design a methodological strategy for the recovery of the Cultural Heritage of the Cerro municipality, integrating the three Main Processes of the University (PSU) from the integrator workshop Project 4th year of the School of Architecture. The opportunity is offered by the felt need of the population of the municipality of El Cerro and government interest.It applies what is defined as integral practice (PI). The problem arises from the shortcomings of the "know-how" in the Cujae what in theory is defined and accepted as the integrationist approach of the PSU.The main results are: the modeling methodology comprehensive strategy practice and products. It concludes that a comprehensive practice that articulates the substantive processes reconfigures all its components according to the integral formation of students, teachers and community members to the extent that promotes university-company communication.Keywords: integral practices, university principal process, integral academic formation in superior education.